Pengaruh Motivasi Kerja, Stres Kerja dan Lingkungan Kerja Terhadap Organizational Citizenship Behavior - Yulianto, Mochamad Rizal; Errinda Ayu Dwi Pramesti; Lilik Indayani; Alshaf Pebrianggara (Universitas Maritim AMNI Semarang, 2023)
This study aims to determine the effect of work motivation, work stres, and work environment on organizational citizenship behaviour at PT. Sari Murni Jaya.The population used is the production employees of PT. Sari Murni Jaya, amounting to 60 people, and in this study 60 people were sampled. The sampling technique used in this study was simple saturated sampling. Data collection was carried out by distributing questionnaires. To test the hypothesis, multiple linear regression analysis tools are used, multiple correlation coefficient (R), multiple determination coefficient (R2), classical assumption test, F test and t test with the help of SPSS statistic 25.0, as well as validity and reliability tests. The results of the validity and reliability tests showed that all items of the questionnaire were declared valid and reliable because the rcount value was greater than the rtable value.The results of this study prove that work motivation influences organizational citizenship behavior (OCB),work stres also influences organizational citizenship behavior (OCB), work environment influences organizational citizenship behavior (OCB), In addition, work motivation, work stres and work environment simultaneously influence on organizational citizenship behavior (OCB).